2011
DOI: 10.1039/c0ee00713g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the research of polyanion-type cathode materials for Li-ion batteries

Abstract: In the past decades, research efforts on polyanion-type cathode materials by the scientific community intensified significantly. This paper reviews the latest advances in the exploration and development of polyanion-type compounds as high performance cathode materials for Li-ion batteries. It focuses on the synthesis, structure and physicochemical (especially electrochemical) properties of several classes of polyanion compounds. The relationship between composition-structure-performance of the novel electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
315
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(329 citation statements)
references
References 228 publications
10
315
0
4
Order By: Relevance
“…31 Moreover, in an attempt to enlarge the electrochemical stability window of the electrolyte and enable the investigation of the Ni redox activity at higher potential values, an ionic liquid-based electrolyte, that is, NaTFSI in Py 13 FSI (1:9 in mole ratio), was employed. 32,33 A comparative electrochemical investigation between the carbon-coated Na 4 Ni 3 (PO 4 ) 2 (P 2 O 7 ) and Na 2 NiP 2 O 7 is shown in Figure 3, showing the differential capacity vs voltage (dQ/dV) curves of Na 4 Ni 3 (PO 4 ) 2 (P 2 O 7 )/C and Na 2 Ni(P 2 O 7 )/C.…”
Section: Resultsmentioning
confidence: 99%
“…31 Moreover, in an attempt to enlarge the electrochemical stability window of the electrolyte and enable the investigation of the Ni redox activity at higher potential values, an ionic liquid-based electrolyte, that is, NaTFSI in Py 13 FSI (1:9 in mole ratio), was employed. 32,33 A comparative electrochemical investigation between the carbon-coated Na 4 Ni 3 (PO 4 ) 2 (P 2 O 7 ) and Na 2 NiP 2 O 7 is shown in Figure 3, showing the differential capacity vs voltage (dQ/dV) curves of Na 4 Ni 3 (PO 4 ) 2 (P 2 O 7 )/C and Na 2 Ni(P 2 O 7 )/C.…”
Section: Resultsmentioning
confidence: 99%
“…LFP's olivine framework enables rapid Li + transport [377], and is stabilised by the electron-withdrawing nature of the PO4 3-polyanion. The strong P-O covalent bond reduces the relative strength of the covalent interaction to the neighbouring Fe, thus lowering the Fe 4+/3+ redox couple energy and providing stable operating voltages of ~3.5 V, with good reversibility [378]. LFP electrodes are also relatively inexpensive to prepare, non-toxic and environmentally benign, all factors which have become increasingly important over recent years.…”
Section: Lifepo4 (Lfp)mentioning
confidence: 99%
“…One such example is LiMnPO4 [447][448][449][450][451][452][453][454][455][456][457][458], which is isostructural to that of olivine LiFePO4, while possessing a higher operating voltage (4.1 vs. 3.5 V, respectively) [378,448], and hence energy densities which could exceed 700 Wh kg -1 . At this point, it should be suggested that LiMnPO4 represents a more realistic candidate compared to LiCoPO4 or LiNiPO4, since the working voltage of LiCoPO4 or LiNiPO4 electrodes (4.9 and 5.1 V, respectively), currently lies outside regions of stability of the commonly-employed organic (carbonate) electrolytes [378]. Early examples of LiMnPO4 electrodes, however, were unable to demonstrate appreciable electrochemical activity [373], until a solid-state reaction involving the addition of carbon black to the reactant mixture enabled a capacity of 140 mA h g -1 to be extracted [448].…”
Section: Other Transition Metal Phosphates (Limpo4)mentioning
confidence: 99%
“…[96][97][98] In addition, polyanionic frameworks are expected to better screen the K-K repulsion in the structure, unlike the layered structure where the strong K-K repulsion limits the K storage capability. [57] In this respect, polyanion materials may be particularly relevant for KIBs.…”
Section: Polyanionic Compoundsmentioning
confidence: 99%